2014
DOI: 10.1002/art.38711
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fucosylation Reshapes Inflammatory Macrophages and Suppresses Type II Collagen–Induced Arthritis

Abstract: Objective Fucosylation catalyzed by fucosyltransferases (FUTs) is an important post-translational modification involved in a variety of biological processes. The purpose of the current study is to determine the roles of fucosylation in rheumatoid arthritis (RA) and the efficacy of reestablishing the immune homeostasis by using 2-Deoxy-D-galactose (2-D-gal), a fucosylation inhibitor. Methods Q-PCR was performed to determine the expression of fucosyltransferases (FUTs) in RA and osteoarthritis (OA) synovial ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 44 publications
7
76
0
2
Order By: Relevance
“…Induction of agalactosylated glycan in total IgG glycome was previously associated with HIV infection and inflammation and was confirmed in our study . In addition, we revealed that certain glycomic alterations that have been associated with inflammation (a loss of disialylated glycans and an increase of fucosylated glycans) and reduction of ADCC activity (an increase of fucosylated glycans), persist during suppressed HIV infection . These glycomic dysregulations may underlie chronic inflammation and immunological dysfunction during suppressed HIV infection thus contributing to the pathogenesis of HIV‐associated comorbidities.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Induction of agalactosylated glycan in total IgG glycome was previously associated with HIV infection and inflammation and was confirmed in our study . In addition, we revealed that certain glycomic alterations that have been associated with inflammation (a loss of disialylated glycans and an increase of fucosylated glycans) and reduction of ADCC activity (an increase of fucosylated glycans), persist during suppressed HIV infection . These glycomic dysregulations may underlie chronic inflammation and immunological dysfunction during suppressed HIV infection thus contributing to the pathogenesis of HIV‐associated comorbidities.…”
Section: Discussionsupporting
confidence: 87%
“…These results confirm some previously reported data and report new IgG glycomic alterations that associate with HIV infection and persist despite suppressive ART. In particular, decreased levels of IgG sialylated glycans, which is associated with proinflammatory activity, and increased levels of IgG fucosylated glycans, which is associated with lower ADCC and higher inflammation, regardless of the ART‐suppression status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of 2-F-Fuc against various diseases was shown in in vivo mouse models of cancer and sickle cell diseases (Belcher et al, 2015; Okeley et al, ). An indirect inhibitor, 2-deoxy-galactose, was also shown to be effective against arthritis (Li et al, 2014). These studies underscore the potential of fucosylation inhibitors as direct therapeutics.…”
Section: Discussionmentioning
confidence: 82%
“…7 Progression of OA occurs in conjunction with an increase in pro-inflammatory (M1) macrophages which not only exacerbate articular damage, but also reduce the chondrogenic potential of implanted MSCs. 4, 8 …”
Section: Introductionmentioning
confidence: 99%